Permeability study of Several Soil Types in Sunggal Sei Krio District and in PTPN II Tanjung Morawa District Deli Serdang Through Laboratory and Field test - Sarip Muda Siregar; Sumono Sumono; Lukman Adlin Harahap (Universitas Sumatera Utara, 2014)
Permeability of the soil is one important factor in designing drainage channels. The determination of soil permeability can be done in the field and in laboratory. The research was aimed to determine the value of permeability rate in Sei Krio Alluvial, Entisol, and Ultisol soils in PTPN II Tanjung Morawa thorugh laboratory and field tests. Results of laboratory studies showed that the rate of permeability on Alluvial, Entisol, and Ultisol soils were, 4.39 cm/hour, and 2,14 cm/hour respectively. The value of permeability rate in the field on Alluvial, Entisol and Ultisol soils were 3.45cm/hour, 4,12 cm/hour, and 2,01 cm/hour respectively. Factor affecting the permeability differences between the three types of soil were effective depth and porosity of the soil. Differences in soil permeability in laboratory and in the field were because of the thickness of the soil. Keywords: Permeability, Effective Depth, Porosity, Drainage.